2012
DOI: 10.1590/s0034-89102012000500001
|View full text |Cite
|
Sign up to set email alerts
|

Internações hospitalares por causas sensíveis à atenção primária no Distrito Federal, 2008

Abstract: OBJECTIVE:To analyze hospitalization rates due to ambulatory care-sensitive conditions. METHODS:The study used data from the Hospital Database of the Brazilian National Health System corresponding to the Federal District in the year of 2008. The main diagnosis for hospitalization was analyzed based on the International Classifi cation of Diseases, and absolute frequency, proportion and coeffi cient were calculated according to causes, age groups and sex. RESULTS:The ambulatory care-sensitive conditions (ACSC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 13 publications
3
15
0
12
Order By: Relevance
“…Generally speaking, the positive association between admissions for PCSCs and age extremes in this study has also been identified in other studies 9,10 . Among younger individuals, this highlights the higher admissions rates for PCSCs in the 1 to 4 year age bracket, compared to infants (< 1 year).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Generally speaking, the positive association between admissions for PCSCs and age extremes in this study has also been identified in other studies 9,10 . Among younger individuals, this highlights the higher admissions rates for PCSCs in the 1 to 4 year age bracket, compared to infants (< 1 year).…”
Section: Discussionsupporting
confidence: 89%
“…Heart failure was identified as the second leading cause of admissions for PCSCs in the country, with 16.8 per 10,000 inhabitants in 2006 2 . Heart failure was also identified as the second cause of admissions for PCSCs in a study in the Federal District (Brasilia), with 14.4 admissions per 10,000 inhabitants in 2008, mainly in males and in the 60 and older age bracket 10 . A study from 1995 to 2004 in Pelotas, Rio Grande do Sul State, found that heart failure was the leading cause of admissions for PCSCs in males during eight of the ten years studied 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the average hospitalization rate was 157.6 for each 10,000 males but 165.1 per 10,000 females, i.e., values lower than those observed in Pelotas in 2012 19 . Nonetheless, admission rates in Pelotas were still lower than those found in the states of Campo Grande, Mato Grosso do Sul 20 , and in the Federal District 21 . Analysis by age and causes of admission shows that HPCSC were higher among those under 1 year and points to a decline in other age groups.…”
Section: Discussionmentioning
confidence: 63%
“…A condução dos serviços da APS é condição essencial para que gestores possam, nos diversos âmbitos do sistema de saúde, conduzir os serviços por meio de medidas e tomada de decisão adequadas (27,41) . (25) . Além disso, o pacto pela saúde propõe superar a fragmentação das políticas e programas de saúde, por meio da estruturação de redes de maneira solidária e regionalizada de ações e serviços para melhor qualificação do processo de gestão, e tendo a APS como centro dessa rede (4) .…”
Section: Verifica-se Em Todo O País Forte Impacto Nounclassified